A Study of the Feasibility of Xu Yuanchong's Theories of Literary Translation and of His Findings (Global Journal of Human-Social Science, 2020)
By using the method of qualitative analysis, including compar ison, and by analyzing some typical examples, this paper discusses and proves Xu's principle of creative translation and that of excellence, focusing on the feasibility of his three-beauty principle: beauty in meaning, in sound, and in form. The typical examples are analyzed in detail, mainly from the perspective of prosody. Besides, by employing the deductive approach, the paper explores and explains Xu's findings through his translation of classical literature. In addition, the paper emphasizes that the pr inciple of creative translation and that of excellence and the three-beauty criterion are closely associated with one another. The former two help to ensure the implementation of the three-beauty standard. Finally, the paper states that they are all proved to be objective, scientific, practical, and widely applicable.
Keywords: creative translation; excellence; three-beauty principle; feasibility; xu’s findings